Focal hematopoietic hyperplasia of rib, mimicking to fibrous dysplasia - Afrose, Ruquiya; Akram, Mohammad; Alam, Mohammad Feroz; Khalid, Saifullah; Naim, Mohammed (Annals of Pathology and Laboratory Medicine, 2015)
Focal haematopoietic hyperplasia is a rare and localized proliferation of the bone marrow to such an extent that it produces a tumor-like expansion hence called as pseudotumor. Radiologically it presents as an osteolytic expansile mass and may mimics with certain bony tumors. We report a case of Focal haematopoeitic hyperplasia in the 3rd anterior rib of a 45 year old man clinically presenting as a bone tumor and radiologically mimicking to fibrous dysplasia.